1995
DOI: 10.1002/hep.1840210432
|View full text |Cite
|
Sign up to set email alerts
|

Ethane exhalation and vitamin E/ubiquinol status as markers of lipid peroxidation in ferrocene iron—loaded rats

Abstract: Organ damage caused by iron overload has been mostly attributed to iron-induced peroxidation of membrane lipids. Using the ferrocene iron-loaded rat model, we studied ethane exhalation as a direct marker of in vivo lipid peroxidation, as well as concentrations of alpha-tocopherol and ubiquinol 9/10 in liver and plasma as indirect markers of this process. The feeding of a diet enriched with 0.5% TMH-ferrocene up to 31 weeks resulted in a large increase in liver iron concentration to about 25 mg/g wet weight (w … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Plasma and hepatic vitamin E decreased with progressive iron loading (Dresow et al, 1995). There is no consensus on how iron overload (with or without ethanol) influences hepatic vitamin E, but our results are in good agreement with those of others (Brown et al, 1997).…”
supporting
confidence: 95%
“…Plasma and hepatic vitamin E decreased with progressive iron loading (Dresow et al, 1995). There is no consensus on how iron overload (with or without ethanol) influences hepatic vitamin E, but our results are in good agreement with those of others (Brown et al, 1997).…”
supporting
confidence: 95%
“…That a single oral dose of vitamin E attenuates lipid peroxidation in patients on haemodialysis receiving intravenous iron was demonstrated recently (Roob et al 2000). The protecting role of vitamin E in iron induced lipid peroxidation in-vivo has also clearly been demonstrated (Dresow et al 1995).…”
Section: Resultsmentioning
confidence: 97%
“…The liver is the major organ responsible for iron metabolism, and it is therefore the most vulnerable to serious toxicity due to iron deposition (Nielsen et al, 1993;Dresow et al, 1995). Indeed, liver coefficients were previously found to be increased in the rat liver iron overload model .…”
Section: Discussionmentioning
confidence: 97%
“…The excess iron deposition in hepatic parenchymal cells is associated with hepatic injury, fibrosis and ultimately cirrhosis (Powell et al, 1980), and lipid peroxidation has been proposed to be a major mechanism involved in the pathophysiology of hepatic iron overload (Dresow et al, 1995;Valerio and Petersen, 1998). It has also been suggested that iron facilitates the generation of free radicals, which promotes lipid peroxidation, and that this is a significant pathway for damage in carbonyl iron loaded rats Bacon et al, 1986).…”
Section: Discussionmentioning
confidence: 98%